RER1 regulates lipid metabolism in monocytes and macrophages - Yanxia Liu; Sandra Theil; Mohamed H. Yaghmour; Anja Kerksiek; Peng Chen; Ingo G.H. Schmidt-Wolf; Rebecca Barker; Eva Bartok; Dieter Lütjohann; Christoph Thiele; Jochen Walter (Cellular and Molecular Life Sciences)
Abstract Retention in endoplasmic reticulum sorting receptor 1 (RER1) mediates the retention and retrieval of select cargo proteins, and thereby regulates protein transport in the secretory pathway and assembly of distinct protein complexes. Recently, RER1 was implicated in the assembly and subcellular transport of the TREM2-DAP12 immune receptor complex, and its function in intracellular signaling and phagocytosis. However, the role of RER1 in the regulation of immune cell metabolism remained unknown. Here, we demonstrate an important role of RER1 in the lipid metabolism of monocytic and macrophage-like differentiated THP-1 cells. The deficiency of RER1 resulted in the accumulation of lipid droplets (LDs) in both monocytes and macrophage-like cells. Comprehensive mass spectrometry analyses revealed complex changes in the cellular lipid metabolism and the composition of LDs. RNA sequencing revealed an important role of RER1 in the regulation of genes related to lipid metabolism. Further, western immunoblotting confirmed an important role of RER1 in the expression of select key proteins involved in cellular lipid metabolism. The combined data indicate that RER1 plays an essential role in lipid metabolism in monocytes and macrophages.